(untitled) (Research, Society and Development, 2022)
Depression is a disease that affects mental health that basically comes from the modern lifestyle. Several approaches are used to treat depression, from psychotherapy, sport and pharmacological therapies. This study aimed to discuss the use of sertraline to treat depression, pointing out its pharmacodynamics, efficacy and adverse effects. Sertraline belongs to the group of drugs known as selective serotonin reuptake inhibitors (SSRIs) that are commonly prescribed for the treatment of depression, panic attacks, obsessive-compulsive disorders and post-traumatic stress disorder. Treatment with sertraline does not produce significant change in cognitive and psychomotor functions. Through the information collected, it was observed that sertraline has a positive effect in the first six weeks of treatment, especially in relation to the reduction of anxiety. The drug is also effective in the treatment of postpartum depression, being commonly used for this part of the population.